Synthesis, Characterization of Some New Heterocyclic Derivatives - Asstabraq Mohsin Yasir (Journal of Global Pharma Technology, 2018)
The newly compounds containing a seven-member ring oxazepane and five-member ring tetrazole derivatives were prepared starting schiff bases. Synthesized by percyclic reactions of imine group with phthalic anhydride resulted the formation of 1,3-oxazepane-4,7dione derivatives (S1, O). The new tetrazole derivatives were obtained from treatment of each prepared schiff bases S and S1 with sodium azide to give derivatives (S2, T). Finally derivatives have been characterized by melting points, FT.IR and 1H-NMR spectroscopy.Keywords: Phathalic anhydride, Sodium azide, Tetrazole, Oxazepane-4,7dione.